Increased Arctic influence on the midlatitude flow during Scandinavian Blocking episodes. (19th November 2019) - Day, Jonathan J.; Sandu, Irina; Magnusson, Linus; Rodwell, Mark J.; Lawrence, Heather; Bormann, Niels; Jung, Thomas
Abstract: Recent studies have suggested that Arctic teleconnections affect the weather of the midlatitudes on time‐scales relevant for medium‐range weather forecasting. In this study, we use several numerical experimentation approaches with a state‐of‐the‐art global operational numerical weather prediction system to investigate this idea further. Focusing on boreal winter, we investigate whether the influence of the Arctic on midlatitude weather, and the impact of the current Arctic observing system on the skill of medium‐range weather forecasts in the midlatitudes is more pronounced in certain flow regimes. Using so‐called Observing System Experiments, we demonstrate that removing in situ or satellite observations from the data assimilation system, used to create the initial conditions for the forecasts, deteriorates midlatitude synoptic forecast skill in the medium‐range, particularly over northern Asia. This deterioration is largest during Scandinavian Blocking episodes, during which: (a) error growth is enhanced in the European‐Arctic, as a result of increased baroclinicity in the region, and (b) high‐amplitude planetary waves allow errors to propagate from the Arctic into midlatitudes. The important role played by Scandinavian Blocking, in modulating the influence of the Arctic on midlatitudes, is also corroborated in relaxation experiments, and through a diagnostic analysis of the ERA5 reanalysis and reforecasts. Abstract : Change in RMS error (%) for z 500 in the IN‐SITU OSE (top) and Arctic relaxation experiment (bottom) at a lead time of 1 day (T+24; left) and 4 days (T+96; right), with respect to the control for each experiment. Forecasts were started at 0000 and 1200 UTC between 1 December 2017 and 31 March 2018. The operational ECMWF HRES analysis is used to verify the forecast skill. The regions where (a, b) in situ data are denied and (c, d) relaxation is performed, are shown in magenta. The north Asia region is shown in red.